Militia Movement in Tangerang Incident of 1946 - Rilva Deni Yogatama; Moh. Ali Fadillah; Yuni Maryuni (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
This research aimed to determine the role of the militia movement in a bloody incident in Tangerang Regency known as the Tangerang Incident in 1946. To achieve this goal, this study utilizes historical research methods and relevant theories to understand events through found historical sources. Historical sources used are oral and written. Based on the time when these historical sources were produced, these historical sources are subdivided into primary historical sources in the form of contemporary books, archives, photographs and newspapers. While secondary historical sources are interviews, relevant books and research. Based on the research results, Tangerang Regency is a multi-ethnic area where these conditions are prone to inter-ethnic riots, inter-ethnic conflicts have often occurred in this area since 1913 and relations between communities are getting worse. In a chaotic situation, militia groups emerged which were built on the interests of certain ethnic groups that were mutually hostile to one another, the group eventually committed an inhumane act known as the 1946 Tangerang Incident. This incident lasted for nearly two months between 1 June 1946 and July 15, 1946 where this incident claimed hundreds of lives through acts of robbery, murder and arson. even categorized as one of the bloodiest events of that era.